Effect of Formaldehyde on the Immunochemical and Biological Activity of Staphylococcal Endotoxin B - Silverman, Sidney J. (1969)
Staphylococcal enterotoxin B was treated with 0.15 or 0.3% formaldehyde at 37 C and pH 7.3. As early as 8 hr after addition of HCHO, the toxin was unable to precipitate as much antibody from antiserum as untreated toxin; greater amounts of treated toxin were required to reach equivalence and to inhibit precipitation. With increasing time, its reactivity decreased so that at 32 weeks it could precipitate only 20% as much antibody as untreated toxin. When other factors were kept constant, the degree of inactivation increased as the HCHO concentration increased from 0.6 to 1.4%. Treated toxin gave a “reaction of partial identity” by the Ouchterlony double-immunodiffusion technique. The emetic effect of the toxin for the monkey remained essentially unchanged for about 48 hr of treatment, but the amount required to cause death by the intravenous route increased from 25 to over 1,000 μg/kg of body weight. HCHO destroyed the pyrogenic effect for rabbits. The treated toxin remained immunogenic for rabbits even after 4 to 5 weeks of exposure to 0.3% HCHO at 37 C.